Revitalisasi Nilai-Nilai Keushuluddinan Melalui Media Sosial Di Era Digital 5.0 - Aulia, Guruh; Qalby, Nur (Tasamuh: Jurnal Studi Islam, 2025)
The Digital Era 5.0 is marked by the integration of artificial intelligence, technology personalization, and high connectivity in human life, including in the religious realm. This article discusses how social media can be a strategic tools in revitalizing the values ​​of ushuluddin which include aspects of monotheism, morality, and transcendental awareness. Using a qualitative approach through literature studies and critical discourse analysis, this article reveals that social media can be an interactive, participatory, and cross-generational preaching space. However, its use also presents challenges in the form of a flood of religious information, the spread of intolerant ideologies, and the reduction of the meaning of religious teachings due to symbolic commodification. Therefore, revitalizing the values ​​of ushuluddin on social media requires strong digital literacy, adaptive religious communication strategies, and active collaboration from religious figures, academics, and digital communities. These findings emphasize the importance of making social media not just a tools, but a new spiritual space that supports the development of people's religiosity in a contextual and transformative manner.